Business-Level Strategy Analysis and Planning Case: "Ducreme" Startup Company - Putra, Gregorius Damai; Dhewanto, Wawan (Journal of Business and Management, 2016)
Abstract - The first year of startup business operated is a crucial year where the business success rate is low. The success of a startup business is determined by business-level strategy that can be implemented to existing market condition and market competition. Food and beverage business in Bandung is very competitive, so startup company need the right strategy in order to survive in this competitive market. Ducreme is a startup company that was established in February 2015. The Ducreme's vision is to create acceptable innovative food and beverage products to satisfy customers so that it can enter the national retail market in the future. The main product of Ducreme is milk tea with six variant flavors.This research is made to analyze the startup business-level strategy, and the results of the strategy's implementation to the performance of business startup for the first year its operates. Ducreme choose to implement differentiation strategy due to its strength to create innovative product. In general, Ducreme can grow in food and beverage market that is already competitive and its products can be accepted by customers. The results of this analysis showed that the startup company's sales performance is very depended on the distributor. The positive impact of the cooperation with the distributor is a broader marketing area coverage to reach more customers. The negative impact of this dependence is the decline in sales when there are problems happen to distributor so they canâ€™t perform in sales. Culinary exhibition also gives a significant impact on sales because of greater margin obtained due to price mark-up.After analyze and make conclusions on the Ducreme performance, the author make recomendation of business and functional-level strategy plan for the second year based on the results of the performance analysis in the first year by considering company internal condition. This strategy is expected to increase Ducreme performance in order to face competitive market.In 2016, Ducreme choose to implement focused differentiation strategy in order to maximize their strength in already competitive market. Ducreme wants to develop new product in sachet package ready to brewed. This product will be targeted to B2B customers. The market size of this product is not large enough compared to the mass market that has been taken by the product in bottle package, but it is more profitable market in terms of quantity and sales turnover if Ducreme could established cooperation with the B2B customer.For the existing bottled-product recommendations; (1) Ducreme should participate in more culinary event to gain more profit and to increase brand awareness, (2) Ducreme should try another marketing methods so that do not rely only on existing channels. This recommendation to avoid decreasing in sales due to reseller/distributor problem, (3) Ducreme should increase the number of channel distribution to increase more sales, (4) Ducreme should optimize its social media because it has not been fully utilized to increase brand awareness, and (5) Ducreme should try to increase brand awareness by using the selebgram endorse.For the planned sachet product recommendations; (1) Ducreme should develop a product that is acceptable to B2B market segment. This should consider quality and price level acceptance of customers, (2) Ducreme should create a list of potential B2B prospects that are ready to be product sampled before product launched to the market, (3) Feedback generated is used to develop products to fit with the majority of the target marketâ€™s preference, and (4) Ducreme should spread product proposals and product samples to the target market, and follow up who interested to products.Keywords: Business-level Strategy, Functional-level Strategy, Business Performance, Startup BusinessÂ